Evaluation of soil nutrient characteristics in Tianshan Mountains, North-western China. (October 2022) - Tudi, Muyesaier; Li, Hongying; Li, Hairong; Wang, Li; Yang, Linsheng; Tong, Shuangmei; Yu, Qiming Jimmy; Ruan, Huada Daniel
Highlights: Soil nutrient index method was used to gain a comprehensive insight of soil nutrient characteristics of Tianshan Mountains. The average soil nutrient indices of the western area were higher than those of the eastern area. All nutrients except the total salts decreased with increasing depth. The differentiations of soil nutrients and variation patterns were attributed to the vegetation type and coverage, altitude, and more importantly, to human activity. Abstract: Background: Soil nutrients are the basic properties and essential characteristics of the soil. Study of areal variability of soil nutrients is an important fundamental work for regional planning, environmental protection, and regionally sustainable development. Dynamic changes in soil nutrients are affected by factors such as soil type, fertilization, farming, irrigation, altitude, and climate. This study takes the Tianshan Mountains, located in the central region of Xinjiang, China, as this region is not only a hub for agriculture, industry, transportation, and tourism, but also it is crucial as a forest-grassland transition zone. Purpose: Through field sampling, laboratory analysis and supported by statistical analysis, we investigated the soil nutrient characteristics and the soil nutrient index to gain a spatial image of soil nutrient status in Tianshan followed by the discussion of those influencing factors. Methods: We selected suitable locations along the forest-grassland transition zone to excavate pits of 40 cm × 40 cm in area and 100 cm in depth. A total of 133 soil samples were collected from 0–5 cm, 5–20 cm, and 20–40 cm in pairs (woodland, grassland). Five soil nutrients (soil organic matter (SOM), available nitrogen (AN), available phosphorus (AP), available potassium (AK) and total salts were selected for experimental, multivariate statistical, correlation and soil nutrient index analyses. Result and discussion: The results show that (1) the average soil nutrient indices of the western area (M-T and K-B sites) were 0.5 and 0.24, respectively, higher than 0.2 of the eastern area (B-A site); (2) in soil layers of different depths of these three locations, all nutrients except the total salts (SOM, AN, AP, and AK) decreased with the increase in depth; (3) more fertile soils distribute in the western area (M-T and K-B sites) than in others of the Tianshan Mountains, showing higher soil nutrient contents and nutrient indices, abundant vegetation with greater diversity, higher vegetation coverage (80%-90%), and higher altitude. Conclusion: It can be concluded that the differentiation of soil nutrient index between western and eastern section of Tianshan were attributed to theirs' vegetation type and coverage, altitude, and more importantly, human activity. .